2021
DOI: 10.19161/etd.915678
|View full text |Cite
|
Sign up to set email alerts
|

Yaşlı yetişkinlerde sarkopeni prevalansı ve yaşam kalitesi: Türkiye’nin doğusundan bir araştırma

Abstract: Aim: Sarcopenia as a geriatric syndrome decreases quality of life and increases functional dependency, hospitalization and mortality. The aim of this study is to investigate the prevalence of sarcopenia among community-dwelling people aged 65 years and older in Muş province and to examine its effects on quality of life. Materials and Methods: In this study we have interviewed 371 community-dwelling older adults. A total of 186 older adults from the rural area and 185 older adults from Muş city center were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
3
0
2
Order By: Relevance
“…In hospitalized patients the prevalence is 14.7%, in nursing home residents the prevalence is 59%, in community residents the prevalence ranges from 12.9-40.4%, and in cancer patients the prevalence is 38.6% [13]. The prevalence of sarcopenia was found to be 11.8% among elderly Turkish individuals living in rural areas; it was 21.6% in among Turkish individuals living in urban areas [14]. A meta-analysis of 1578 patients with different hematological malignancies revealed that 39.1% of patients with lower overall survival were sarcopenic [15].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In hospitalized patients the prevalence is 14.7%, in nursing home residents the prevalence is 59%, in community residents the prevalence ranges from 12.9-40.4%, and in cancer patients the prevalence is 38.6% [13]. The prevalence of sarcopenia was found to be 11.8% among elderly Turkish individuals living in rural areas; it was 21.6% in among Turkish individuals living in urban areas [14]. A meta-analysis of 1578 patients with different hematological malignancies revealed that 39.1% of patients with lower overall survival were sarcopenic [15].…”
Section: Discussionmentioning
confidence: 86%
“…Sarcopenia is a common disease worldwide, and it is especially prevalent in elderly populations [11,14]. It is also associated with sex, disease status and comorbidities, and the type and duration of treatment (e.g., high-dose chemotherapy and steroids) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Values at a 95% confidence level, 5% margin of error, and 11.8% of the population proportion were used for calculations, with a sample size of a minimum of 160 participants needed for this study. Considering the losses-by taking 20% more participants-210 participants were included in this study [35].…”
Section: Sample Sizementioning
confidence: 99%
“…Örneklem büyüklüğü (Epi Info TM Hastalık Kontrol ve Önleme Merkezi, Atlanta, Georgia, ABD) programında, 86.539 toplam 65 yaş üzeri nüfus üzerinden, diz osteoartrit prevalansı %24,8, sarkopeni prevalansı %16,7 olmak üzere %5 hata payı ve %95 güven aralığıyla hesaplandı. [20][21][22] Alt ekstremite cerrahisi geçirenler, son 6 ay içinde intraartiküler girişim yapılanlar, inflamatuar romatolojik hastalığı bulunanlar, santral veya periferik sinir sistemini etkileyebilen inme, nörodejeneratif hastalıklar, polinöropati, multipl skleroz gibi hastalığı olanlar, kognitif disfonksiyonu olanlar, denge ve propriyoseptif duyuyu etkileyebilen diabetes mellitus, tiroid fonksiyon bozuklukları, B12 vitamin yetersizliği, kronik böbrek yetersizliği gibi endokrin, metabolik veya sistemik hastalığı olanlar, sandalyeden kalkma testini yapamayacak kadar şiddetli sarkopenisi olanlar, fizik muayenede bağ laksitesi veya eklem hareket açıklığında kısıtlılık tespit edilenler araştırmaya dâhil edilmedi. Araştırma öncesi, araştırma protokolü Sivas Cumhuriyet Üniversitesi Girişimsel Olmayan Klinik Araştırmalar Etik Kurulu tarafından onaylandı (tarih: 20 Aralık 2020, no: 2020-12/11), katılımcıların yazılı ve sözlü onamları alındı, araştırma süresince Helsinki Bildirgesi ve İyi Klinik Uygulamalar Kılavuzu kurallarına uyuldu.…”
Section: Gereç Ve Yöntemlerunclassified